2014
DOI: 10.1111/anu.12128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of probiotic on performance and intestinal microflora of Chinese soft-shelled turtle(Trionyx sinensis)

Abstract: This experiment was conducted to study the effect of dietary supplementation of probiotic on performance and intestinal microflora of Chinese soft-shelled turtle. Healthy Chinese soft-shelled turtles (6000 pieces with average weight of 5 g) were selected and randomly divided into two groups: control and treatment with three replicates each. The control was fed on normal basal diet, whereas treatment was fed on basal diet supplemented with 1 9 10 8 cfu.g À1 Bacillus subtilis preparation. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…The role of probiotics is controversial. Benefits, including the ability to increase the abundance of Firmicutes, have been noted in other chelonians [37,38], however a study in mice and humans found that probiotics delayed return to normal gut microbiome composition post-antibiotics [39]. As next generation sequencing capabilities become more readily available and affordable, it is foreseeable that there will come a time when the fecal microbiome may be a practical diagnostic test that can be used to tailor the diet for optimum microbial composition.…”
Section: Discussionmentioning
confidence: 99%
“…The role of probiotics is controversial. Benefits, including the ability to increase the abundance of Firmicutes, have been noted in other chelonians [37,38], however a study in mice and humans found that probiotics delayed return to normal gut microbiome composition post-antibiotics [39]. As next generation sequencing capabilities become more readily available and affordable, it is foreseeable that there will come a time when the fecal microbiome may be a practical diagnostic test that can be used to tailor the diet for optimum microbial composition.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrosequencing of intestinal microbiome showed lower microbial diversity and an increase of Firmicutes due to antimicrobial compounds production by B . subtilis [ 57 ]. It is consistent with our theory which suggests that, in turtles, microbiota quantitative and qualitative reduction may lower direct competition within the host and bacteria for nutrients and result in better growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…TR provided by Ningbo Traditional Chinese Pharmaceutical Co., Ltd. (Ningbo, China) was milled into 60 mesh powder. A total of 800 g turtle feed per pool was prepared daily into granules in accordance with a standard diet formula which contained fish 62%, wheat starch 22%, soybean meal 7%, yeast powder 5%, vitamin mix 2%, and mineral 2% (w/w) (Zhang et al, 2014), and spread into each pool allowing turtles to ingest freely twice (400 g in the morning and 400 g in the evening) every day. The basal diet (control) contains 65% of marine fish powder, 24% of starch, and 2% of yeast, salt, amino acids, vitamins and minerals.…”
Section: Dietsmentioning
confidence: 99%
“…To increase the survival rate and improve the quality of the SST, the effects of nutrients, such as lipids (Perez-Casanova et al, 2010), vitamin A (Chen LP and Huang, 2015), vitamin C (Wang and Huang, 2015), vitamin E (Zhou et al, 2004), magnesium (Chen LP and Huang, 2015), and probiotics (Zhang et al, 2014), on feeding SST have been investigated in recent years. At the same time, the effects of farming environmental factors such as incubation temperatures (Dang et al, 2015), Bacillus thuringiensis fatal infections (Chen et al, 2014), and acute ammonia toxicity (Ip et al, 2008) on SST were also observed.…”
Section: Introductionmentioning
confidence: 99%